the 4th power on the outside applies to each factor of the inside
(3y^8/2zy^2)^4
= 3^4 y^32/(2^4 z^4 y^8)
= 81y^24 / (16z^4)
or you could have reduced the y's first
(3y^8/2zy^2)^4
= (3y^6/(2z))^4
= 81y^24/(16z^4)
The power of a quotient rule - simplify
(3y^8/2zy^2)^4
I need help in solving this problem - I do know to solve what is in the parentheses first. by the 4th power...but I need detailed guidance in order to grasp the concept - ty:)
3 answers
Got it - ty:0)
My next one I think I have figured out - however do we simplify the 10^10?
9x10^-4/3x10^-6 = 3x10^10
My next one I think I have figured out - however do we simplify the 10^10?
9x10^-4/3x10^-6 = 3x10^10
Sorry - this is regarding computations w/scientific notation